2010
DOI: 10.1159/000321504
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myelogenous Leukemia Patients Are at Low Risk for Invasive Fungal Infections after High-Dose Cytarabine Consolidations and Thus Do Not Require Prophylaxis

Abstract: We evaluated the frequency of invasive fungal infections (IFI), the frequency of empirical antifungal use (EAFU), and the efficacy of fluconazole prophylaxis on IFI and EAFU after high-dose cytarabine (HiDAC) consolidations. Twenty-seven acute myelogenous leukemia patients in their first complete remission received 76 cycles of HiDAC (median cycle: n = 3). Fluconazole prophylaxis was administered following 44 cycles (fluconazole group) and not given in 32 cycles (control group). IFI (2 episodes) + EAFU (11 epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 81 publications
(85 reference statements)
1
15
2
1
Order By: Relevance
“…The choice of fluconazole/itraconazole as comparators to voriconazole/posaconazole was based on clinical trial experience. 6 That consolidation chemotherapy is low risk for IFD (affecting 3 of 27 patients) compared to post-induction aplasia 1,16,22 suggests review of our universal policy of broad-spectrum prophylaxis may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of fluconazole/itraconazole as comparators to voriconazole/posaconazole was based on clinical trial experience. 6 That consolidation chemotherapy is low risk for IFD (affecting 3 of 27 patients) compared to post-induction aplasia 1,16,22 suggests review of our universal policy of broad-spectrum prophylaxis may be warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Although the studies we discuss here have significant differences in patient size (small or large), center number (single or multicenter), type of study (prospective or retrospective), and geographical place (Europe, USA, or Japan), these study results are remarkably consistent [4][5][6][7][8]. No study reported increased mortality by increased number of HiDAC cycles.…”
mentioning
confidence: 59%
“…The number of platelet and red blood cell transfusions [5,7] and duration of thrombocytopenia [7] remained stable throughout the HiDAC cycles [5,7]. Documented fungal infections [8], empirical intravenous antifungal use [8], duration of antibiotic use [7], and the frequency of pneumonia [5] were similar between HiDAC cycles. No accumulated central nervous system, hepatic, or renal toxicity reported during HiDAC cycles [5,7].…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The infectious diseases society of America (IDSA) recommends antibiotic prophylaxis using a fluoroquinolone in high-risk patients, i.e., those leukemia patients with expected neutropenia >7 days [7]. Consistently, AML patients who have short neutropenia duration (e.g., post-consolidation) do not benefit from antifungal prophylaxis [8]. These guidelines recommend antifungal prophylaxis against Candida infections in patients undergoing intensive remission-induction or salvage-induction for acute leukemia, and antiviral prophylaxis for herpes simplex virus (HSV) in patients undergoing leukemia induction therapy.…”
Section: Discussionmentioning
confidence: 99%